Implementasi Pengajian Al-Badariyah Terhadap Perilaku Keagamaan di Desa Bajubang Laut, Batanghari - Izzatun Nuraini (JIGC (Journal of Islamic Guidance and Counseling), 2021)
One of the things that is often held in an assembly is the recitation of mothers. This is because basically women are the most important figures in the household. If a woman has a good understanding of the Islamic aspects, of course this will be very good in the household. A Muslim woman will be the first teacher for her children and makmum for her husband. Of course, women must have a foundation of religious knowledge. This study uses a qualitative approach with a descriptive approach. The location of this research was carried out at the Al Badariyah Ta'lim Council, Bajubang Laut Village, Muara Bulian District, Batanghari Regency. The results of the study, the researchers saw that not all members of the Al-Badariyah study applied adab in the study. The findings of this study include the following: (1) The implementation of Al-Badariyah recitation activities in Bajubang Laut Village, has been carried out systematically with a congregation of 50 people. (2) The supporting factor for Al-Badariyah recitation activities is that the majority of the surrounding population is Muslim, so the presence of missionaries is also supported. While the inhibiting factor in the implementation of the recitation is the lack of self-awareness of some members of the importance of recitation activities, coupled with the tight schedule of taking care of their respective households, (3) The impact of recitation activities consists of two aspects, namely increasing insight into hablumminallah and habluminnas.